Envisioning sustainable sanitation planning: a unified approach of diffusion of innovation and theory of planned behavior in predicting ecosan toilet adoption in Arba Minch City, Ethiopia - Ejigu, Abrham Kassa; Yeshitela, Kumelachew (Frontiers in Environmental Science, 2024)
This study explores the adoption of ecological sanitation (ecosan) toilets in Arba Minch City, Ethiopia, using an integrated approach combining the diffusion of innovation (DOI) model and the Theory of Planned Behavior (TPB). The research aims to understand the complex associations between DOI variables (relative advantage, complexity, compatibility, trialability, and observability) and TPB constructs (attitude, subjective norm, and perceived behavioral control) in predicting residents' behavioral attitudes and intentions. Applying Structural Equation Modeling (SEM) and bootstrapping techniques, the study investigates direct and indirect effects, offering a comprehensive analysis of the adoption process. The objectives include examining the influence of TPB and DOI constructs on residents' intentions, unraveling direct and indirect effects on these intentions, and investigating variations among users of different toilet types in the city. The result of the study shows that attitude and perceived behavioral control are central to shaping intentions, aligning with TPB principles. Contextual factors like compatibility, relative advantage, and trayability reveal nuanced insights, deviating from conventional patterns. The study identifies attitude as a key moderator between DOI constructs and behavioral intention, enriching our understanding of the adoption process. In conclusion, the integrated DOI and TPB model provides nuanced perspectives on factors influencing behavioral attitudes and intentions toward ecosan toilet adoption. The crucial roles of perceived behavioral control and attitude underscore the importance of tailored interventions. The study's insights are relevant for policymakers, practitioners, and development organizations working on sustainable sanitation practices in urban areas, contributing to broader sustainable development objectives.